Rainforests - Hardie, Robert; Classroom Video (New South Wales : Classroom Video)
Provides an overview of the Australian rain forest, discussing structure, the role of light and water, soils, climate, nutrient recycling, fauna and vegetation, use of rain forests for resources, and the future of the rain forest. Suggested audience: primary, intermediate, junior secondary
Writer, Robert Hardie
Presenter: Richard Morecraft
VCD format
Keywords: Rain forest ecology